2018
DOI: 10.1353/lib.2018.0036
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Determinants of Scholarly Book Prices in the Fields of Science, Technology, and Medicine

Abstract: This empirical study examines long-term and current book market trends and important factors affecting scholarly book prices in science, technology, and medicine (STM). It analyzes the market demand, supply, and prices of STM books and how they affect academic libraries' budgets. A semilogarithmic econometric model is formulated to explore the factors that affect STM book prices. Various product features, including book length, cover type, format, supplier types, and publication locations, are examined. The em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…However, Liu et al (2018) found that in the 14 science, technology and medicine subject areas they looked at, the price differential between print and electronic formats was greatest in the medical, nursing, health and psychiatry category (2.33 times) compared to 1.88 for all categories.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Liu et al (2018) found that in the 14 science, technology and medicine subject areas they looked at, the price differential between print and electronic formats was greatest in the medical, nursing, health and psychiatry category (2.33 times) compared to 1.88 for all categories.…”
Section: Discussionmentioning
confidence: 99%
“…Liu, Gee and Terng (2018) compared ebook and print book prices in 14 subject areas within science, technology and medicine, but did not compare the prices for the ebook and print book formats of the same title nor did they separate out medical books from other health sciences titles. They found that ebooks in the field of ‘medical sciences, nursing, health sciences and psychiatry’ were on average, 2.33 times as expensive as print books.…”
Section: Introductionmentioning
confidence: 99%